Linking adverbials in applied linguistics research articles: a corpus-based study - Danilo Duarte Costa (2015)
This study aims at investigating the use of linking adverbials (Biber et al., 1999) in research articles written by Brazilian English L2 applied linguists in comparison to those written by English L1 professionals of the same field. Two comparable corpora have been compiled for this study, namely CRAB (Corpus of Research Articles written by Brazilians) and CRAN (Corpus of Research Articles written by Natives), both containing more than 300,000 tokens. The corpora compilation process followed strict methodological procedures basedon Biber (1993) and McEnery et al. (2006).The data, after undergoing the Log-Likelihood statistical test, were analysed using the software AntConc 3.4.2 for a qualitative examination. Seven different semantic categories of linking adverbials were investigated so as find similarities and differences in the use of those linguistic elements between the two corpora.The results show that there are significant differences in the use of linking adverbials in Brazilian academic writing in comparison to native speakers. These differences are in both frequency of use (over and underuse of some forms) and the way in which the linking adverbials are employed in texts. In addition, we have found that there are adverbials which are, at times, misused by Brazilian writers.